Quality Improvement of Low Pressure Flush Column Reflux Pumps Using PDCA Method: A Case Study in an Urea Plant - Heri Kurniawan; Gde Windar Lesmana; Muhammad Asrol (President University, 2023)
This study focuses on the problems in the use and maintenance of centrifugal pumps at PT Pupuk Kalimantan Timur (PKT) in Indonesia. This study specifically looks at the 110-J pump, which is critical to the production process as its failure can result in a shut down of the factory. The study analyzes the history card of the pump over the period of 2015 to 2021 and identifies that there have been multiple repairs due to high vibration, shaft bending, and other internal damage caused by differences in throat bushing sizes. The study calculates that the average loss due to these issues is around IDR 122,012,857 annually and that the repair work takes about 5 working days. The study uses quality improvement tools plan, do, check, action (PDCA) identify the problems and formulate improvement efforts to increase the usage period and reduce maintenance costs. This study is important for improving the reliability of the production process and ensuring the availability of urea and NPK fertilizer, particularly in Indonesia. Result of this research is the decrease in the frequency of pump repairs from 3.7 times per year to none and accelerate pump assembly from 5 days to 3 working days.Keywords: Centrifugal pumps, shaft bending, maintenance, quality improvement tools, vibration